A Bridge to the Job Market: The Urgency of Curriculum Policy at Institut Agama Kristen Negeri (IAKN) Ambon - Lani Tomasila (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2025)
This policy paper describes that comprehensively identifies and analyzes the issue of misalignment between the competencies of IAKN Ambon graduates and job market needs. The main problems outlined include three aspects: an unadaptive curriculum, minimal strategic collaboration with industry, and suboptimal human resource development policies for lecturers. The current curriculum focuses too much on theory, with rigid governance, minimal labor market data, and weak initiative from study program units. This is exacerbated by limited institutional collaboration with the industrial sector, private companies, and non-governmental organizations, resulting in students lacking practical experience and professional insight. Furthermore, lecturer competency development is not a top priority, hampering teaching innovation and research relevance. This paper uses qualitative methods with a descriptive analysis approach and literature review. The author collected and reviewed data from various primary and secondary sources, such as scientific journals, books, research reports, and relevant online articles. The collected data were analyzed descriptively to identify root causes and interrelated patterns, then synthesized to formulate a coherent argument. Thus, this abstract presents a holistic picture of the challenges faced by IAKN Ambon and provides a basis for future improvement efforts.